Awareness, perceptions of and compliance with tobacco control policies among naswar vendors in Khyber Pakhtunkhwa Pakistan. Issue Volume 31:Issue e2(2022) (5th July 2021) - Ahmad, Fayaz; Khan, Zohaib; Siddiqi, Kamran; Khan, Muhammad Naseem; Kibria, Zeeshan; Forberger, Sarah; Bauld, Linda; Kanaan, Mona; Zeeb, Hajo
Abstract : Introduction: Regulatory compliance in the retail environment is integral to the success of tobacco control. We assessed compliance among naswar (smokeless tobacco product widely used in South Asia) vendors with tobacco control laws. We also assessed their awareness of tobacco-related harms and policies and perceived effect of policies on their sales. Methods: We surveyed 286 naswar vendors in three districts of the Khyber Pakhtunkhwa province of Pakistan. We recruited general and specialty vendors from urban and rural areas through multistage cluster sampling. Compliance was measured for promotion, sale to/by minors and tax paid on naswar. We used logistic regression analyses for assessing the association between the outcome variables (awareness of tobacco harms and laws, perceptions about the effect of policies on business and compliance with laws) and their predictors. Results: Most vendors (70%) were aware of tobacco-related harms of naswar. Although educated vendors were more aware of tobacco control policies, the greatest awareness was for a ban on sales to/by minors (21% overall). The majority of vendors (76%) violated this policy (measured by self-report), and violations were more common among rural than urban vendors (OR 2.27, 95% CI 1.05 to 4.96). Most vendors (71%) violated a ban on promotion of naswar. Vendors perceived tax increases and sales ban to/by minors as most detrimental for business. Conclusions: There was poor awareness and compliance among naswar vendors in Pakistan with tobacco control laws. This study finds potential areas for policy interventions that can reduce urban/rural disparities in implementation of and compliance with tobacco control laws.